THE EFFECT OF USING THE CONCEPT MAPPING STRATEGY ON THE ACHIEVEMENT OF SIXTH-GRADE PRIMARY SCHOOL STUDENTS IN SCIENCE - Duaa Reda Dakhel (Scholars Digest Publishing, 2025)
The research aims to identify the effect of using the concept mapping strategy on the achievement of sixth-grade primary school students in science. This study was conducted in Iraq. The research sample consisted of (90) students. To achieve the research objective, the researcher formulated a null hypothesis and adopted the experimental method with partial control, with two equivalent groups, one experimental and the other a control group, with a post-test for achievement. The researcher intentionally selected the research sample, which was Sumer Elementary School for Girls. The research group was selected using a simple random drawing method, and the two research groups were statistically rewarded. The researcher also prepared the research requirements and research tool, represented by the achievement test, which consisted of (40) multiple-choice test items. Its apparent validity and content validity were verified, and the reliability of the achievement test items was determined using two methods: split-half and Internal consistency. The researcher implemented the experiment during the second semester (2024-2025). The results showed that students in the experimental group, who studied using the concept mapping strategy, outperformed students in the control group, who studied using the traditional method, in achieving science subjects. In light of the research results, the researcher presented a set of conclusions, recommendations, and proposals.
Keywords: Strategy - Concept Maps - Achievement - Science - Sixth Grade Primary School.